2004
DOI: 10.1080/1361126042000183075
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring in black and white: the intricacies of cross‐cultural mentoring

Abstract: Cross-cultural mentoring relationships can be sites of struggle around the issues of race, class and gender. In addition, the mentor/protégé relationship offers micro-cosmic insight into power relations within western society. The authors of this paper, a black woman associate professor and a white male professor, use the example of their mentoring relationship to illustrate six common issues facing academicians involved in these relationships: (1) trust between mentor and protégé;(2) acknowledged and unacknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 17 publications
5
92
0
Order By: Relevance
“…A considerable body of research exists on the issue of gender and race matching in mentoring relationships, with 18.5% of the articles reviewed referring to this issue. Some studies have found that matching increases mentee and mentor satisfaction levels (Bowman & Bowman, 1995;Johnson-Bailey & Cervero, 2004;Sands et al, 1991). These findings also show that the career-related and psychosocial needs of under-represented or marginalized groups can be best responded to through race and gender matching.…”
Section: Prerequisites For the Student Peer Mentormentioning
confidence: 56%
See 4 more Smart Citations
“…A considerable body of research exists on the issue of gender and race matching in mentoring relationships, with 18.5% of the articles reviewed referring to this issue. Some studies have found that matching increases mentee and mentor satisfaction levels (Bowman & Bowman, 1995;Johnson-Bailey & Cervero, 2004;Sands et al, 1991). These findings also show that the career-related and psychosocial needs of under-represented or marginalized groups can be best responded to through race and gender matching.…”
Section: Prerequisites For the Student Peer Mentormentioning
confidence: 56%
“…Interestingly, this review of articles points to the importance of shared values as an aspect of personality (Bouquillon et al, 2005;Pitney & Ehlers, 2004), a shared world view (Johnson-Bailey & Cervero, 2004;Rose, 2005), or congruent beliefs (Bouquillon et al, 2005) as enabling the mentee to identify with their mentor. McDougall and Beattie (1997) describe the concept of complementarity as a shared or common value base between mentor and mentee.…”
Section: Supportivenessmentioning
confidence: 99%
See 3 more Smart Citations